2017
DOI: 10.1039/c7nr02499a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine substitution enhances the self-assembling ability of hydrogelators

Abstract: When supramolecular hydrogels are applied as tissue culture scaffolds, their mechanical strength and biocompatibility are the two most important factors that must be considered. However, systematic studies on the structure-mechanical property (or structure-cytotoxicity) relationship of hydrogels are rare. Herein, we rationally designed three hydrogelators and their corresponding phosphate precursors, and systematically studied their self-assembling ability and cytotoxicity. The results indicated that fluorine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…With the radiative transition of 1 I 6 1 D 2 , and 1 G 4 energy levels, the released photons are absorbed by CDs, resulting in afterglow emission. In addition, Wu et al [171] adopted the same strategy to achieve multicolor afterglow under 980 nm excitation by one-step in situ introduction of upconversion luminescence into CDs composites.…”
Section: Radiative Energy Transfermentioning
confidence: 99%
“…With the radiative transition of 1 I 6 1 D 2 , and 1 G 4 energy levels, the released photons are absorbed by CDs, resulting in afterglow emission. In addition, Wu et al [171] adopted the same strategy to achieve multicolor afterglow under 980 nm excitation by one-step in situ introduction of upconversion luminescence into CDs composites.…”
Section: Radiative Energy Transfermentioning
confidence: 99%
“…This work, being the first case of using 19 F NMR/MRI to sense the activity of tyrosine kinase and phosphatase, underscores the importance of incorporating ENS into a dynamic process. In related studies, 356,357 Liang et al also reported the use of liquid-phase scanning tunneling microscopy (L-STM) to directly visualize enzymatic self-assembly/disassembly of nanofibers of an analogue, in which F replaces the CF 3 group in 85.…”
Section: Enzymatic Noncovalent Synthesis In Cell-free Conditionsmentioning
confidence: 99%
“…Their results indicated that the integration of EISA and subcellular targeting processes could synergistically killing cancer cells without acquired drug resistance. Wu et al introduced fluorine substitution to the precursors to enhance their self-assembling ability as well as anticancer capability . However, the therapeutic effect of these agents are still incomparable to the commonly used anticancer drugs.…”
Section: Recent Advances Of In Situ Nanodrug Preparationmentioning
confidence: 99%
“…Wu et al introduced fluorine substitution to the precursors to enhance their self-assembling ability as well as anticancer capability. 48 However, the therapeutic effect of these agents are still incomparable to the commonly used anticancer drugs. Doxorubicin and taxol always show IC 50 values less than 10 μM toward various cancer cell lines.…”
Section: ■ Introductionmentioning
confidence: 99%